Nano Alumina Radiation Effect on Thermo-Mechanical Properties of High Density Polyethylene-Hydroxyapatite Composite - Mustaffa, Nurul Akmil (2011)
This study aims to investigate the effect of nano alumina and radiation on the mechanical and thermal properties of high density polyethylene hydroxyl apatite (HDPE/HA) composite. Nano alumina was produced by using sol-gel method. Nano alumina was analyzed by using XRD, FTIR and TEM to confirm the spectroscopy of alumina and size. Percentage of HA was studied to get the optimum mechanical strength. The tensile strength was studied by varying the percentage of HA in the HDPE blend. Percentage of HA that has been used in this study were 10, 20, 30wt% with respect to the weight of matrix. The 10 wt% and 20wt% of HA indicate the better tensile strength compare to 30wt% of HA. Before nano alumina can be used as filler in the polymer matrix, (3-methacryloxypropyl) trimethoxysilane (MPS) was used to functionalize the nanoparticles due to its bi-functional nature: hydrolysable group (–Si(OCH3)3) and unsaturated carbon–carbon double bond. Percentage of silane used in this study is from 1 % to 5 % to the amount of matrix. At 4 % silane, tensile strength shows the best result compare to the other percentages. The effect percentage of nano alumina in the HDPE was studied by using 1 to 5 % of nano alumina to the amount of the HDPE. It is proved that the silane gives favorable effect to HDPE/nano alumina composite at 4% wt to the weight of matrix. The composite was irradiated to improve tensile properties. Subsequently, the composite was irradiated by using electron beam accelerator. Mechanical, thermal, and morphological properties were characterized. The mechanical properties result showed at 100KGy irradiation dose the tensile, flexural and impact strength increased as well as hardness value. The tensile fracture surfaces of the composites were characterized by using SEM and confirmed the tensile results. From the flexural analysis, the presence of nano alumina (with 4% MPS) in the composite (HDPE/HA) has insignificant increment on both flexural strength and flexural modulus. Impact strength for notched izod impact test was increased at the 4% percentage of nano alumina loading. The DMA result showed the Tg of the HDPE is shifted to the lower temperature after addition of HA, nano alumna and silane. The Tg of composite have n significant changes after irradiation. However, the irradiation has increased the storage and loss modulus. Lastly, DSC results showed the crystallinity of pure HDPE, composite 0 KGy, and composite 100 KGy was 47.08, 41.42, and 50.72 respectively.